Aboriginal and Torres Strait Islander people and digital inclusion: what is the evidence and where is it?. Issue 2 (3rd April 2019) - Rennie, Ellie; Thomas, Julian; Wilson, Chris
ABSTRACT: Quantitative research on digital inclusion has grappled with significant gaps in data with respect to Aboriginal and Torres Strait Islander people. We compare the survey methods and questions of the Australian Digital Inclusion Index (ADII) data, the National Aboriginal Torres Strait Islander Social Survey (NATSISS) and the Census of Population and Housing to identify these gaps. While the ADII is the most comprehensive examination of digital inclusion, encompassing access, affordability, and digital ability measures, the general ADII dataset excludes Aboriginal and Torres Strait Islander people living in remote areas. In addition, we draw together findings from qualitative research on digital inclusion within particular Aboriginal and Torres Strait Islander communities, to demonstrate why digital choices—including the preference for mobile devices—are important for understanding statistical trends.